2017
DOI: 10.1038/s41598-017-04934-9
|View full text |Cite
|
Sign up to set email alerts
|

Large perturbations in CO2 flux and subsequent chemosynthesis are induced in agricultural soil by the addition of elemental sulfur

Abstract: The microbial contribution to soil organic matter has been shown to be much larger than previously thought and thus it plays a major role in carbon cycling. Among soil microorganisms, chemoautotrophs can fix CO2 without sunlight and can glean energy through the oxidation of reduced elements such as sulfur. Here we show that the addition of sulfur to soil results in an initial surge in production of CO2 through microbial respiration, followed by an order of magnitude increase in the capture of carbon from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Nevertheless, this study showed a less significant negative effect of nano-S on the GOassociated aerobic carbon mineralization benefits than in the previously conducted pot experiment (Hammerschmiedt et al, 2022), which showed a very strong negative effect of the nano-S + GO. In line with these results, Kelleher et al (2017) referred to an initial surge in the production of CO 2 through microbial respiration, which was followed by increased capture of carbon dioxide as elemental sulfur was oxidized to sulfate (Kelleher et al, 2017). The conditions set up in this experiment did not promote complete nano-S-mediated attenuation of GO stimulation.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Nevertheless, this study showed a less significant negative effect of nano-S on the GOassociated aerobic carbon mineralization benefits than in the previously conducted pot experiment (Hammerschmiedt et al, 2022), which showed a very strong negative effect of the nano-S + GO. In line with these results, Kelleher et al (2017) referred to an initial surge in the production of CO 2 through microbial respiration, which was followed by increased capture of carbon dioxide as elemental sulfur was oxidized to sulfate (Kelleher et al, 2017). The conditions set up in this experiment did not promote complete nano-S-mediated attenuation of GO stimulation.…”
Section: Discussionsupporting
confidence: 73%
“…In line with these results, Kelleher et al. (2017) referred to an initial surge in the production of CO 2 through microbial respiration, which was followed by increased capture of carbon dioxide as elemental sulfur was oxidized to sulfate ( Kelleher et al., 2017 ). The conditions set up in this experiment did not promote complete nano-S-mediated attenuation of GO stimulation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, this process is slow and occurs in a gradual manner (CARRIÓN et al, 2008). Also, Kelleher et al (2017) showed that elemental sulphur applied in the soil initially results in the production of CO 2 through microbial respiration, followed by order of magnitude increase in the capture of carbon from the atmosphere.…”
Section: Discussionmentioning
confidence: 99%